Tafsir Rasa Dalam Puisi Linguistik Cinta Karya Misnawati Untuk Mengurai Kata-Kata Penuh Makna - Anwarsani Anwarsani; Santa Santa; Enisyahwate Enisyahwate; Juhairiyani Juhairiyani; Tuti Adithama; Nabila Salwa (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The aim of this research is (1) to describe the poem "Linguistic of Love" by Misnawati in depicting the feelings of love. (2) to describe the emotional nuances reflected in each stanza of Misnawati's "Linguistic of Love" poem and its correlation with language selection. The results of this research indicate that Misnawati successfully created a work that is not only aesthetic but also radiates emotional power capable of connecting readers with the essence of love. Through beautiful romanticism and precise language choices, this poem invites us to reflect on and feel the beauty and complexity of the feelings of love, grounded in linguistic principles.